2023
DOI: 10.3390/vetsci10080528
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Measuring Serum Amyloid A Concentration in Japanese Black Cattle in Clinical Practice

Urara Shinya,
Osamu Yamato,
Yuka Iwamura
et al.

Abstract: This study investigated the concentration of serum amyloid A (SAA), an acute phase protein, in Japanese Black cattle. Four practical trials were performed to evaluate the transition of SAA and sialic acid before and after dehorning, the relationship between the SAA concentration and other blood test parameters, the SAA dynamics in the diseased cattle, and the blood test results, including the SAA concentrations, of the two cases with a follow-up. The SAA concentration increased with dehorning but decreased 7 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
0
2
Order By: Relevance
“…Measured concentrations of plasma haptoglobin and SAA concentrations in this study were in part much higher than reported in previous field studies on the diagnostic utility of these biomarkers ( 24 , 30 , 31 , 56–59 ). This may partially be due to the inclusion of a highly preselected study population of second-opinion cases referred to a university teaching hospital, which may create a bias toward more severely affected cases.…”
Section: Discussioncontrasting
confidence: 80%
“…Measured concentrations of plasma haptoglobin and SAA concentrations in this study were in part much higher than reported in previous field studies on the diagnostic utility of these biomarkers ( 24 , 30 , 31 , 56–59 ). This may partially be due to the inclusion of a highly preselected study population of second-opinion cases referred to a university teaching hospital, which may create a bias toward more severely affected cases.…”
Section: Discussioncontrasting
confidence: 80%
“…Measured concentrations of plasma haptoglobin and SAA concentrations in this study were in part much higher than reported in previous field studies on the diagnostic utility of these biomarkers (24, 30,31,[56][57][58][59]. This may partially be due to the inclusion of a highly preselected study population of second-opinion cases referred to a university teaching hospital, which may create a bias toward more severely affected cases.…”
Section: Discussioncontrasting
confidence: 68%